Development, Characterization and Pharmacological Investigation of Umbelliferone Conjugates of NSAIDs - B, NIJA; Rasheed, Arun; Kottaimuthu, A (Iraqi Journal of Pharmaceutical Sciences, 2021)
The present investigation developed the ester prodrugs of Non-steroidal anti inflammatory drugs (NSAIDs), Mefenamic acid and Flurbiprofen by conjugating with the natural antioxidant, 4-methyl umbelliferone that resulted the formation of Mefenamic acid-umbelliferone ester prodrug and Flurbiprofen-umbelliferone ester prodrug .The principal objective this study is the synthesis of the ester prodrugs of NSAIDs with the enhanced therapeutic activity and minimized side effects. Prodrugs were synthesized by coupling method using N,N’- dicyclohexylcarbodiimide/4-dimethylaminopyrimidine, subjected to physical, chemical characterization, spectral characterization (IR, 1H NMR, 13C NMR and Mass spectra),hydrolysis-kinetic study and pharmacological evaluation such as anti-inflammatory, ulcerogenecity as well as the effect of the NSAIDs in the central nervous system against degenerative mechanisms. The current study revealed that the umbelliferone conjugates of NSAIDs which upon administration would release the parent drug as a result of enzymatic or non-enzymatic hydrolysis in the desired site with enhanced anti inflammatory activity and reduction in the gastro intestinal toxicity. Also the synthesized pordrugs showed enhanced brain targeting efficiency with protective action against the degenerative processes.